Robust impedance control of a hydraulic suspension system - Fateh, Mohammad Mehdi (International journal of robust and nonlinear control, 2010)
A novel robust impedance control approach is developed to control dynamic behavior of a vehicle subject to road disturbances. This behavior is predetermined as an impedance rule to achieve passenger comfort and vehicle handling by the use of a hydraulically actuated suspension system. Impedance control law is simple, free of model and efficient to apply for a broad range of road conditions. Moreover, it relates comfort to handling. This control approach can provide a desired comfort when passing a bump, and both desired comfort and handling after passing a bump. Robust position and force controls are used to implement the robust impedance control with the presence of uncertainties. A transformed proportional–integral–derivative control is proposed to perform the robust control. The system stability is analyzed and analytical results are confirmed by simulations. A quarter‐car model of suspension system and a nonlinear model of hydraulic actuator are used to simulate the control system. Copyright © 2009 John Wiley & Sons, Ltd.